2015
DOI: 10.1016/j.ijid.2015.06.025
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of body weight-based vancomycin therapy and the incidence of nephrotoxicity: a retrospective study in the northwest of China

Abstract: The data from this study indicate that a vancomycin dosage >38mg/kg/day and a serum trough level >20mg/l are both independent factors associated with the development of nephrotoxicity, suggesting that renal function should be monitored closely during vancomycin treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 44 publications
1
10
0
Order By: Relevance
“…Patients' clinical parameters were extracted mainly based on previous studies. 3,6,7,9,[12][13][14][15][16][17][18][19][20][21][22][23]26,27…”
Section: Data Extractionmentioning
confidence: 99%
“…Patients' clinical parameters were extracted mainly based on previous studies. 3,6,7,9,[12][13][14][15][16][17][18][19][20][21][22][23]26,27…”
Section: Data Extractionmentioning
confidence: 99%
“…This study is the first large scale investigation of VA-AKI in Hong Kong. In previous studies, the incidence of VA-AKI in Chinese varied from 2.4 to 45% [9,[13][14][15][16] (Additional file 1: Table S1). The difference of estimated incidence is due to different populations, sample sizes, inclusion criteria and AKI definition.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that the incidence of vancomycin-induced nephrotoxicity varies in a range from 5% to 43%, and depends on the trough level (approximately double at the trough level of >15 mg/l compared to the trough level of 15 mg/l: 25% vs. 12%) (van Hal et al, 2013). In a study by Dong et al (2015), patients given a weight-based dose (20-45 mg/kg/day) developed nephrotoxicity at an incidence of 15.6%. The present study showed that the use of vancomycin led to mild changes in renal function based on BUN, SCr, and eGFR levels, but nephrotoxicity only developed with a lower incidence of 5.9%.…”
Section: Discussionmentioning
confidence: 99%